2006
DOI: 10.1021/jf060219i
|View full text |Cite
|
Sign up to set email alerts
|

Selection, Characterization, and CDR Shuffling of Naive Llama Single-Domain Antibodies Selected against Auxin and Their Cross-Reactivity with Auxinic Herbicides from Four Chemical Families

Abstract: Indoleacetic acid (IAA)-binding single-domain antibodies (sdAbs) were isolated from a naive phage-display library constructed from the heavy chain antibody repertoire of a Ilama. The highest-affinity sdAb isolated (CSF2A) had a K(D) of 5-20 microM for two IAA-protein conjugates and a K(D) of 20 microM for free IAA. This sdAb also bound to a synthetic auxin analogue, 1-naphthaleneacetic acid (NAA), and to six auxinic herbicides (K(D) values of 0.5-2 mM), but not to serotonin and tryptophan, which are structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Several proteins have been found to bind auxin amongst which is the relatively poorly studied Auxin Binding Protein (ABP). Authors hypothesized “that antibodies that bind to IAA may be used as surrogate ABPs to study the structure-activity relationships of IAA and the auxinic herbicides binding to their putative receptor.” In this work [17], authors isolated five different sdAbs from a naïve llama library with relatively low affinity for the IAA-BSA conjugate (K d ≥ 5 µM) as determined by SPR (surface plasmon resonance). Inhibition experiments with sdAb CSF2A (K d = 5 µM) revealed broad cross-reactivity with all auxinic herbicides with IC 50 values > 200 µM for herbicides and 800 µM for IAA.…”
Section: Summary Of Vhh Assays To Environmental Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several proteins have been found to bind auxin amongst which is the relatively poorly studied Auxin Binding Protein (ABP). Authors hypothesized “that antibodies that bind to IAA may be used as surrogate ABPs to study the structure-activity relationships of IAA and the auxinic herbicides binding to their putative receptor.” In this work [17], authors isolated five different sdAbs from a naïve llama library with relatively low affinity for the IAA-BSA conjugate (K d ≥ 5 µM) as determined by SPR (surface plasmon resonance). Inhibition experiments with sdAb CSF2A (K d = 5 µM) revealed broad cross-reactivity with all auxinic herbicides with IC 50 values > 200 µM for herbicides and 800 µM for IAA.…”
Section: Summary Of Vhh Assays To Environmental Chemicalsmentioning
confidence: 99%
“…Another example comes from the same group, where five selected anti-auxin VHH clones were shuffled by staggered extension process (StEP). Although none of the shuffled clones had better affinity toward auxin than the best original clone, the affinity toward auxinic herbicides was significantly decreased [17]. Recently an interesting study investigating the structure – binding relationship of an anti-methotrexate (anti-MTX) VHH antibody was published by Fanning and Horn [49, 23].…”
Section: Advantages Of Vhhsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations for single-domain antibodies indicated that despite the heavy chain variable fragments (V H ) lack of variable light and heavy chain pairing, they also can recognize and bind a wide variety of epitopes and antigen types (Nguyen et al, 2000;van der Linden et al, 2000;Sheedy et al, 2006;Doyle et al, 2008). Moreover, some research on the catalytic antibody also indicated that the heavy chain was found to be the determining factor for catalytic efficiency (Ulrich and Schultz, 1998).…”
Section: Preparation Of the Human Single-domain Abzyme Se-scfv-2d8-v mentioning
confidence: 99%
“…Others have focused on creating naive phage display libraries from which it is theoretically possible to extract binders for a nearly boundless number of targets (15,16); however, naive libraries may possess only low-affinity binders. While most applications require high-affinity binders, lower affinity binders may provide the starting point for affinity maturation.…”
Section: Introductionmentioning
confidence: 99%